The role of sports participation in the association between students' body image concerns and disordered eating - Vaiva Balčiūnienė; Rasa Jankauskienė; Miglė Bacevičienė (Lithuanian Sports University, 2021)
Background. Body image concerns (BICs) negatively influence young people's health as they mutilate psychosocial functioning and lifestyle. The present study aimed to compare BICs, socio-cultural attitudes towards appearance, and disordered eating (DE) in a large sample of student women and men of different body mass (BMI) and physical activity and to evaluate the mediating role of sports participation in the association between BICs and DE. Methods. A total sample of 1850 students (1087 or 58.8% were women, average age 21.6 ± 5.0 years) participated in the study and completed a questionnaire measuring BICs, internalization of the socio-cultural appearance ideals, drive for muscularity, DE, physical activity (PA), and BMI. Two hundred eighty-two men and two hundred eighty-eight women reported leisure-time participation in sports. Two-way ANOVA was conducted to test gender, BMI group, and sports participation effects on study variables. Moderated leisure-time exercise at a sports club effects were tested in the association between body image concerns (BICs) and disordered eating behaviours (DE). Results. Overweight/obese students reported greater BICs, internalization of the stereotyped appearance ideals, and DE compared to students of normal body weight. Participants of sports clubs demonstrated higher appearance evaluation and body areas satisfaction; however, they reported higher overweight preoccupation, internalization of socio-cultural ideals, drive for muscularity (men), and DE. A higher level of BMI, BICs, internalization of socio-cultural body ideals, and drive for muscularity (in men) were associated with greater DE in students. Participation in sports was not a significant moderator between BICs and DE. A significant interaction effect between BMI and exercising at a sports club was observed in women. Conditional effects demonstrated that female students with higher BMI and exercising at a sports club were at higher risk of DE (β = .18, p < .001) than women non-exercising at a sports club (β = .13, p < .001). Conclusions. Overweight students of both genders reported greater BICs and DE. Sports-involved students (men and women) demonstrated more favourable body appearance evaluation. However, sports participants of both genders demonstrated greater BICs and DE compared to non-exercisers. Sports participation had no significant mediating power on the associations between BICs and DE; however, women with higher BMI and participating in leisure-time sports faced a greater risk for DE than women with higher BMI but not participating in sports. The promotion of a positive body image was important to students, especially female students with higher BMI and participating in leisure sports. Keywords: body image concerns, disordered eating, physical activity, sport clubs, emerging adults.